2021
DOI: 10.1126/science.abe4688
|View full text |Cite
|
Sign up to set email alerts
|

Formation of α clusters in dilute neutron-rich matter

Abstract: The surface of neutron-rich heavy nuclei, with a neutron skin created by excess neutrons, provides an important terrestrial model system to study dilute neutron-rich matter. By using quasi-free α cluster–knockout reactions, we obtained direct experimental evidence for the formation of α clusters at the surface of neutron-rich tin isotopes. The observed monotonous decrease of the reaction cross sections with increasing mass number, in excellent agreement with the theoretical prediction, implies a tight interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…[30] for the 212 Po problem could be improved with locally-peaked Gaussians. A systematic analysis of the degree of the alpha clustering near the nuclear surface is interesting as it has recently been realized in alphaknockout reactions on Sn isotopes [52].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] for the 212 Po problem could be improved with locally-peaked Gaussians. A systematic analysis of the degree of the alpha clustering near the nuclear surface is interesting as it has recently been realized in alphaknockout reactions on Sn isotopes [52].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…[33] but no information other than its existence is available. Mass measurements have been done up to 57 Ca [34], and the charge radii [35] have been determined up to 52 Ca, and recently interaction cross sections have been measured up to 51 Ca [36]. It was conjectured by the coupled-cluster calculation that the neutron dripline of Ca isotopes is around 60 Ca [37] and 62 Ca has two-neutron halo structure with dominant s-wave [18].…”
Section: Introductionmentioning
confidence: 99%
“…The role of α particles in supernova explosions has attracted attention [6]. Very recently, an interesting indication that α clusters emerge in a surface region of medium-heavy mass nuclei have been obtained by a systematic measurement via the α knockout reactions [7]. These encourage us to study the formation and structure of an α particle in dilute neutron-rich matter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the α knockout (p, pα) reaction has been established as a quantitative probe for the α clustera e-mail: masaaki@nucl.sci.hokdai.ac.jp ing at nuclear surface [4,5,6,7], and using this reaction, the α cluster formation at the surface of Sn isotope chain has been measured for the first time [8]. It has been shown that the knockout cross section monotonically decreases in neutron-rich Sn isotopes indicating the negative correlation between the neutron skin formation and α clustering.…”
Section: Introductionmentioning
confidence: 99%